The Level of Self-Efficacy and Self-Esteem of Students with Learning Disabilities Towards the Mastery of Soft Skills - Muhammad Bakaruddin, Nurul Awanis; Ab Halim , Fazlinda (Research and Innovation in Technical and Vocational Education and Training, 2024)
This study involves the self-efficacy and self-esteem of students with learning disabilities towards the mastery of soft skills among students from Vocational Special Education Secondary Schools in Malaysia, focusing on students enrolled in two schools' food preparation and production courses. This survey research distributed 56 questionnaires to students with learning disabilities. The research findings indicated moderate mastery of soft skills, self-esteem, and self-efficacy. Students' self-efficacy and self-esteem levels can be enhanced through various efforts from multiple parties. The soft skills of students can be nurtured through different encouragements and approaches. Teachers need to pay more attention to students with learning disabilities by designing various activities and teaching materials suitable for the cognitive level of these students in school.